O Código Nacional de Processo Administrativo Tributário: segurança jurídica. - Teti, Célia Aparecida Souto Barros (2022)
The present work has os its centrais questioning the diversity and normative profusion of the tax administrative process in the national federation and proposes a uniformity by a national law. The objective of the work is to validate the feasibility and relevance of a national code of constitutional process based on the application of the principle of legal certainty and the legislative legislation in the applicable system in the creation of a national complementary law. according to art. 146, III of CF/88. The question is; "according to the current constitutional system, is it possible and relevant to the construction of the national code of administrative procedure?" A dogmatic legal study was carried out in order to verify the administrative feasibility in the Brazilian Constitution and in the legislative legislature for the construction of a code of the tax process, through politicization within the scope of the Tax Administration system, by standardizing the administrative tax content. Whose arose was that of the arts. 21, I and art. 24§§ 1st to 4th which describes the rules alongside the tax legislation the tax administrative process of art. 146, III of CF/8, which support the standardization of the national instrumental process, in the sense that the relationship is one that is born, developed and extinguished according to rules. The law applied in the methodology was the theoretical-based review of legal principles and legal principles for the research in relation to the data and legal principles the normative review for the particular process, following the reference to the data and principles to legal principles to the administrative process, as a qualitative study of administrative decisions by federal and state judges in Pernambuco was also carried out, in the context of impartiality and public administrative efficiency. The study concluded that according to art. 24, I, XI § 1" combined with art. 146, III of the federal constitution, the National Tax Administrative Procedure can be created by enacting a national law of general tax rules, stabilizing and standardizing the formal and instrumental tax process.